AKRUAL DISKRESIONER PADA PERUSAHAAN PUBLIK DI INDONESIA YANG MENGALAMI PERGANTIAN DIREKTUR - Ramadhanti, Wita (Profit: Jurnal Adminsitrasi Bisnis, 2008)
Abstract This research is intended to know whether there are or not earnings management surrounding director turnover. Discretionary accruals based on Jones modified model are used in this research. Data are taken from listed company in Jakarta Stock Exchange that experience executive turnover during 2000 until 2003. This research then classified director changes into routine and non routine. The results show that in routine changes successors upward earnings in the year after executive changes. The successor motives are to proved that he is qualified for his job and also better than his predecessors. On non routine turnover, former director especially from bad performance company, tend to increase earnings to delay or even cancel the possibilities of being fired from their job. The new executives also increase earnings in the year of executive changes to avoid being terminated as their predecessors. Keywords: Earnings management, discretionary accruals, income increasing, income decreasing, director turnover, routine director changes, non routine director changes.